Theoretical insights into the methane catalytic decomposition on graphene nanoribbons edges - Xavier, Neubi F.; Payne, Anthony J. R.; Bauerfeldt, Glauco F.; Sacchi, Marco (Frontiers in Chemistry, 2023)
Catalytic methane decomposition (CMD) is receiving much attention as a promising application for hydrogen production. Due to the high energy required for breaking the C-H bonds of methane, the choice of catalyst is crucial to the viability of this process. However, atomistic insights for the CMD mechanism on carbon-based materials are still limited. Here, we investigate the viability of CMD under reaction conditions on the zigzag (12-ZGNR) and armchair (AGRN) edges of graphene nanoribbons employing dispersion-corrected density functional theory (DFT). First, we investigated the desorption of H and H2 at 1200 K on the passivated 12-ZGNR and 12-AGNR edges. The diffusion of hydrogen atom on the passivated edges is the rate determinant step for the most favourable H2 desorption pathway, with a activation free energy of 4.17 eV and 3.45 eV on 12-ZGNR and 12-AGNR, respectively. The most favourable H2 desorption occurs on the 12-AGNR edges with a free energy barrier of 1.56 eV, reflecting the availability of bare carbon active sites on the catalytic application. The direct dissociative chemisorption of CH4 is the preferred pathway on the non-passivated 12-ZGNR edges, with an activation free energy of 0.56 eV. We also present the reaction steps for the complete catalytic dehydrogenation of methane on 12-ZGNR and 12-AGNR edges, proposing a mechanism in which the solid carbon formed on the edges act as new active sites. The active sites on the 12-AGNR edges show more propensity to be regenerated due lower free energy barrier of 2.71 eV for the H2 desorption from the newly grown active site. Comparison is made between the results obtained here and experimental and computational data available in the literature. We provide fundamental insights for the engineering of carbon-based catalysts for the CMD, showing that the bare carbon edges of graphene nanoribbons have performance comparable to commonly used metallic and bi-metallic catalysts for methane decomposition.